(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the opportunities and existing challenges in modernizing the tourism infrastructure of the Republic of Karakalpakstan. It discusses processes that need to be implemented to enhance the tourism potential of the region, create new opportunities, and bring more economic benefits to the local economy. It highlights the decrees and initiatives of the President aimed at developing tourism in Karakalpakstan. Despite creating opportunities in tourism services, transport, hotels, tourist attractions, natural resources, and cultural heritage sites, challenges in infrastructure and service delivery may slow down progress. This article offers solutions to these issues, focusing on modernizing Karakalpakstan’s tourism sector to diversify the economy, create new jobs, and improve the well-being of the local population.